Investigating measurement variation of modified low-cost particle sensors. (September 2019) - Collingwood, Scott; Zmoos, Jesse; Pahler, Leon; Wong, Bob; Sleeth, Darrah; Handy, Rodney
Abstract: Particulate matter (PM) has demonstrably increased rates of cardiovascular and respiratory related disease; thus, a low-cost sensor that accurately measures PM is desirable including for smaller and more private environments such as residential homes. The low-cost Dylos and the Utah Modified Dylos Sensor (UMDS) have been shown to be highly correlated with references instruments for measuring particle counts and aerosol concentrations, which makes them useful tools for air quality studies. An analytical calibration equation (calibration) is used to describe the linear relationship between the UMDS and a reference instrument, providing the best estimate of PM concentrations when the UMDS is operated. In this study, an investigation of measurement variation of a UMDS was performed using a low-cost calibration technique to determine differences between the brand new UMDS pre-calibration equation (Prec ), a contaminated UMDS post-calibration equation (Postc ), and a cleaned UMDS clean calibration equation (CC). The UMDS were calibrated against a high-grade aerosol spectrometer (Grimm model 1.109) as a reference instrument. Calibrations took place in a home or office environment. Counts per volume units from the UMDS were matched to the Grimm's for comparison. The investigation of the UMDS for measurement variation was performed for the approximate estimates of PM2.5 by using the small bin (i.e. ≥0.50  μm) subtracted from the large bin (i.e. ≥2.5  μm), and for total particulates by using the large bin. Linear regressions were performed between the UMDS and the Grimm per calibration event, which produced R 2 values and slopes that were indicative of measurement variation. Data exceeding the upper limit of quantification (ULOQ) of 106, 000 particles/liter and the lower limit of quantification (LLOQ) of 4 particles/liter were excluded from statistical comparison. R 2 values greater or equal to 0.70 were used to assess measurement variation as a quality control standard for valid comparisons. A rank sum statistical test between calibration comparisons was performed. Prec /Postc and Prec /CC had significant differences indicating measurement variation. Postc /CC did not have any significant differences; cleaning the UMDS had no effect and did not demonstrate measurement variation. Reasons for measurement variation may include instrument contamination (dust/dirt), hardware degradation, altered fan flow rates, and potentially inadequate cleaning of the UMDS. Future work may investigate the rate of measurement variation in order to develop a recommended re-calibration schedule in order to maintain the most accurate estimates of PM for UMDS in long-term operation. Highlights: The Utah modified dylos sensor (UMDS) demonstrated measurement variation in calibration comparisons of new UMDS vs. contaminated UMDS, and new UMDS vs. cleaned UMDS. Measurement variation include inadequate cleaning by the procedure used, degradation of the laser, degradation of the sensor or altered fan flow rates. A reference instrument should be monitored during aerosol calibration measurements to ensure particulate concentrations across the UMDS operational range.